Slow Deep Breathing in Patients Following Double Lumen Catheter Insertion Experiencing Acute Pain Nursing Problems: A Case Report - Muhtadini, Ruqi; Permana, Ryan Hara (Universitas Padjadjaran, 2024)
Inserting a double-lumen catheter (CDL) in hemodialysis patients results in adverse effects, specifically pain. Pain is a disagreeable sensation caused by tissue injury involving sensory and emotional components. Pain management is a nursing care option for individuals experiencing pain. Pain can be managed by non-pharmacological methods, such as the Slow Deep Breathing (SDB) technique. This case study aims to assess the intervention for sleep-disordered breathing in patients with chronic renal disease following central venous catheter installation, focusing on acute pain nursing issues. This article used a case report style focused on a single patient in the treatment room. The effectiveness of the SDB intervention was evaluated by the Numeric Rating Scale (NRS) and by monitoring the patient's blood pressure, pulse, and respiration. The intervention resulted in a decrease in the NRS score from 2 to 0. Additionally, the blood pressure value decreased to normal, the pulse remained within the normal range, and there was no change in the patient's respiratory value for three days post-intervention. Expanding the use of SDB therapies to a more diverse group of patients will enhance the evidence supporting the effectiveness of these interventions.